FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VII - Weldi Rosita Rabbi Rewa; Ninik Indawati; Auliana Farrabanie Al Arsy (Jurnal Riset Pendidikan Ekonomi, 2019)
Learning outcomes are a reflection of the level of success or achievement of the objectives of the learning process that has been carried out and culminated with an evaluation which is then measured using a value or number. This study aims to determine the effect of the implementation of the 2013 curriculum and the full day school system on student learning outcomes in Integrated Social Sciences subjects in VII grade SMP Negeri 17 Malang both simultaneously (simultaneously) or individually (partially). This research is an ex-post facto type and uses a quantitative approach. The population in this study amounted to 168 students of class VII of SMP Negeri 17 Malang with sampling using probability sampling techniques of 70 students. Data collection techniques in this study using questionnaires, interviews and documentation. The results of this study indicate that there is a positive or significant simultaneous effect between the implementation of the 2013 curriculum and the full day school system on student learning outcomes in integrated social studies subjects in class VII SMP 17 Malang. There is a positive or partially significant effect between the implementation of the 2013 curriculum and the full day school system on the learning outcomes of Social Sciences Integrated Class VII SMP Negeri 17 Malang.